Systemic and local immune responses associated with subclinical endometritis in the postpartum diary cow - Foley, Cathriona (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2014)
Activation of local innate immune mechanisms by postpartum bacterial contamination of the uterus occurs in all cows and approximately 30% develop endometritis associated with persistent bacterial infection, inflammation and subfertility. The postpartum period is critical for the restoration of homeostasis within the uterus. However, postpartum cows are in the process of an immune transition between an immunosuppressed state during pregnancy to a requirement for uterine immune activation to clear bacterial contamination within a very short timeframe. In this context, early and efficient activation of local innate immune mechanisms is required. However, the regulation of the innate immune response in the postpartum cow remains to be fully understood. Mechanisms that control inflammation and achieve a physiologically functioning endometrium postpartum while avoiding disease have not been identified.
Keywords: Immunology, Ph.D.; Ph.D. Trinity College Dublin